Graphics Gems V (IBM Version) - Paeth, Alan (Morgan Kaufmann, 1995)
Graphics Gems V is the newest volume in The Graphics Gems Series. It is intended to provide the graphics community with a set of practical tools for implementing new ideas and techniques, and to offer working solutions to real programming problems. These tools are written by a wide variety of graphics programmers from industry, academia, and research. The books in the series have become essential, time-saving tools for many programmers. Latest collection of graphics tips in The Graphics Gems Series written by the leading programmers in the field Contains over 50 new gems displaying some of the most recent and innovative techniques in graphics programming Includes gems covering ellipses, splines, Bezier curves, and ray tracing.